Effect of wing loading on gross takeoff mass of a hybrid buoyant aircraft - UlHaque, Anwar; Asrar, Waqar; Omar, Ashraf Ali; Sulaeman, Erwin; Ali, JS Mohamed (Marques Engineering Ltd, 2016)
Aerostatic lift in a hybrid buoyant aircraft reduces the wing loading as well as the induced drag. This reduction is valid till pressure height. In this paper, the existing analytical relationships for the gross and net mass, as well as wing loading of standard aircraft, are modified to obtain new analytical relationships valid for a hybrid buoyant aircraft. Sail plane wings are chosen for the configuration presented in this work. A simple mission profile for a hybrid buoyant aircraft is chosen. Optimized wing loading is estimated against the specified design constraints for a range of aspect ratios of wings from 15 to 21. Special emphasis is given to the algorithm to be followed for this purpose. Ratio of empty and gross take-off weight is first estimated by using regression analysis. XFLR, a low fidelity tool is used to compute the aerodynamic lift of the wing. The optimum aspect ratio of the wing is estimated. Wing loading and its corresponding net takeoff mass are also computed. The results can be refined further after prediction of realistic aerodynamic data and initial weight estimation.